VMAT2 Inhibitors for the Treatment of Tardive Dyskinesia. (2nd January 2022) - Warren, Barbara; Vanderhoef, Dawn; Johnson, Jessica
ABSTRACT: Psychiatric nurses are at the forefront of optimizing psychiatric care, including educating patients and caregivers on the risks of antipsychotic-induced movement disorders such as tardive dyskinesia (TD). Nurses should be aware that all patients taking antipsychotics should be regularly monitored for the development of TD. Given the current pandemic and increase in telehealth, assessing for TD is challenging; however, evaluation can be successfully completed by implementing the best practices described in this paper. Once TD is diagnosed, nurses can reassure patients that safe and effective FDA-approved treatments for TD (e.g., valbenazine) are now available.